Review on the Use of ICT Driven Solutions Towards Managing Global Pandemics - Navod Neranjan THilakarathne (Journal of ICT Research and Applications, 2021)
A pandemic is a contagious disease outbreak that happens over a large geographic area and affects a great portion of the population while new pathogens appear for which people have less immunity and no vaccines are available. The disease can spread from person to person in a very short time. Health workers are at greater risk of infection because of patients who are carriers. In the 21st century, where everyone is connected through digital technologies, information and communication technology (ICT) plays a critical role in improving healthcare for individuals and larger communities. ICT can be divided into a wide variety of application domains that signify its importance as a major technological paradigm. It is currently drawing large attention because of its potential to alleviate the burden on healthcare systems caused by the rise in chronic diseases, aging populations and pandemic situations. This study surveyed substantial knowledge on how effective ICT healthcare solutions can be used towards managing global pandemics. In order to make it more comprehensive, we also present a four-phase strategic framework that can be deployed to alleviate the strain on healthcare resources during a pandemic, which was derived from the reviewed literature. Further, we also discuss how ICT technologies can be used towards managing pandemic situations chronographically during the transformation from a simple disease outbreak into a global pandemic.